Deprivation and variations in teenage conceptions and abortions in England. Issue 1 (1st January 2005) - Bradshaw, Jonathan; Finch, Naomi; Miles, Jeremy N V
Abstract : There are substantial variations between local authorities in the conception rate of teenagers and the proportion of these that end in abortion. This study builds two deprivation models that explain part of the variation in conceptions and abortions. It then identifies outliers, local authorities with teenage conception and abortion rates that are above or below those predicted by the model. It is suggested that the local authorities with lower than expected conceptions are the ones to look to when seeking to discover how to prevent teenage conceptions and those with higher than expected abortion rates may have abortion services that are more accessible. In general, spatial comparisons of conceptions and abortion should take into account variations in deprivation.